2009
DOI: 10.3928/1081597x-20090707-05
|View full text |Cite
|
Sign up to set email alerts
|

Arcuate Keratotomy for High Postoperative Keratoplasty Astigmatism Performed With the IntraLase Femtosecond Laser

Abstract: Arcuate keratotomy performed with the IntraLase femtosecond laser could be an effective, safe, and relatively predictable treatment of high postoperative keratoplasty astigmatism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
30
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(35 citation statements)
references
References 17 publications
3
30
0
2
Order By: Relevance
“…The mean CI ranged from 0.8 to 0.9. 13,16,[22][23][24][25][26][27][28][29][30][31][32][33] Clinical results from this series compare favorably to other series with similar procedures, reporting a mean CI of 0.9 and a mean surgical-induced astigmatism of 8 D. Our study showed favorable results for reduction of the main cylinder (mean flattening effect, 7.47 6 3.65) and the angle error (mean, 2.2 6 13.1 degrees). Several eyes were overcorrected, creating astigmatism in the opposite direction, but the mean spherical equivalent did not change significantly.…”
Section: Discussionsupporting
confidence: 77%
“…The mean CI ranged from 0.8 to 0.9. 13,16,[22][23][24][25][26][27][28][29][30][31][32][33] Clinical results from this series compare favorably to other series with similar procedures, reporting a mean CI of 0.9 and a mean surgical-induced astigmatism of 8 D. Our study showed favorable results for reduction of the main cylinder (mean flattening effect, 7.47 6 3.65) and the angle error (mean, 2.2 6 13.1 degrees). Several eyes were overcorrected, creating astigmatism in the opposite direction, but the mean spherical equivalent did not change significantly.…”
Section: Discussionsupporting
confidence: 77%
“…These functional results are comparable to results in major clinical studies of regular astigmatism treatment with femtosecond laser-assisted AK. [18][19][20][21][22][23][24][25][26] At the last follow-up, Bahar et al 21 As the predictability results show (Figures 7 and 8), for oblique astigmatism, the mean achieved reduction in cylinder closely approximated the intended reduction at low and high levels of astigmatism; however, overcorrection occurred in negative orthogonal astigmatism, possibly because of the irregular pattern of treatment designed to decrease mainly the irregular compound of astigmatism. As a result, 27.4% of eyes in the present study had no improvement in vision at 2 years compared with 20% at 9.2 weeks, 21 25% at 6 months, 23 and 29% at 7.2 months 24 in earlier studies.…”
Section: Discussionmentioning
confidence: 65%
“…20 This technique is safe and effective for correcting regular astigmatism and is better than manual keratotomy in terms of safety and fewer higher-order aberrations. [21][22][23][24][25] Studies of irregular astigmatism are limited to case series, and there is no report in the literature about the efficacy and safety at 2 years of follow-up. 26 This retrospective study evaluated the safety and efficacy of femtosecond laser-assisted AK to treat irregular astigmatism after PKP during a 2-year follow-up period.…”
mentioning
confidence: 96%
“…Pentacam has been more commonly used in the evaluation of postoperative astigmatism after keratoplasty and further guiding the keratotomy procedure. (Buzzonetti, et al, 2009) Further evaluation of using Pentacam specifically in marginal corneal grafting is warranted.…”
Section: Detection Of Postoperative Astigmatismmentioning
confidence: 99%